Thermo-economic optimization of low-grade waste heat recovery in Yazd combined-cycle power plant (Iran) by a CO2 transcritical Rankine cycle. (15th June 2015) - Amini, Ali; Mirkhani, Nima; Pakjesm Pourfard, Pedram; Ashjaee, Mehdi; Khodkar, Mohammad Amin
Abstract: A transcritical CO2 Rankine cycle is proposed for recovering low-grade waste heat of Yazd combined-cycle power plant in Iran. Each power generation module of this plant consists of two 159 MW Siemens SGT-5-2000E gas turbines and one 132 MW steam turbine. Reducing exhaust gas temperature from 150 °C to 70 °C, the plant can generate excessive power. From thermodynamics approach, it is demonstrated that by fixing the maximum temperature at 145 °C and varying the maximum pressure, the efficiency and the net power output are maximized at Pmax  = 185 bar. In the aforementioned operating point, about 6.3 MW is retained for the selected power plant with a nominal 450 MW of power generation. A more actual case considering thermodynamic losses and economic considerations is then investigated. Genetic algorithm is implanted to conduct a parametric optimization to maximize the benefit-cost ratio which is defined on the basis of total bare module cost and net power output. The results indicate that the cycle costs are more influenced by the maximum pressure rather than the maximum temperature. Through this parametric optimization, the CO2 cycle can produce about 4.04 MW. This is about 0.9% of the plant capacity and increases the total efficiency about 0.4%. Highlights: CO2 transcritical Rankine cycle is used to recover heat in Yazd 450 MW power plant. The cycle behavior is examined as its maximum temperature and maximum pressure vary. 6.3 MW could be retained for the plant on the basis of ideal thermodynamic behavior. Thermo-economic optimization is conducted subject to actual operating conditions. 4.04 MW is recovered considering the actual thermo-economic conditions.